Finite element analysis of a four-cylinder four stroke gasoline engine crankshaft - Parman, S. (EDP Sciences, 2014)
Stress analysis of a crankshaft using traditional method is complicated and needs modification by considering its stress concentration factors. To solve this problem, the crankshaft strength of a four-cylinder four stroke gasoline engine is modeled and analyzed using finite element method (FEM) in this paper. For this purpose, the crankshaft is modeled using CATIA software in detail. Then, the model is imported in ANSYS. In the recent software, the model is meshed into a number of finite elements. After defining the boundary and loading conditions, the stresses occur in the crankshaft are analyzed in order to identify critical locations on it. Â© 2014 Owned by the authors, published by EDP Sciences.